Effects of Rho-kinase inhibition in chronic experimental pulmonary hypertension - Kosanovic, Duro; Justus Liebig University Giessen (My University, 2011)
Pulmonary hypertension (PH) is a severe chronic and life-threatening disease characterized by progressive augmentation of pulmonary arterial pressure that finally leads to right ventricle failure and death. PH has a multi-complex pathology which includes a combination of pulmonary vascular remodelling, vasoconstriction and in situ thrombosis. Key to the severity of the disease is the progressive pulmonary vascular remodelling. The progressive pulmonary vascular remodelling is the attribute of PH pathology and is characterized by abnormalities of vascular cells such as increased proliferation, migration and resistance to apoptosis. Although the PH pathology is the subject of intensive research the precise molecular mechanisms are still not fully understood and successful therapeutic strategy to cure the disease is still needed.An accumulating body of evidence incriminates Rho-kinase (ROCK) in the pathogenesis of PH and suggests the Rho-kinase as a promising therapeutic target. In the line with literature, our study aimed to investigate the therapeutic effects of a novel highly selective and orally active ROCK inhibitor, azaindole-1 in animal models of PH. We successfully demonstrated that azaindole-1 significantly inhibited hypoxic pulmonary vasoconstriction in isolated, ventilated and buffer-perfused murine lungs and proliferation of primary rat pulmonary artery smooth muscle cells in vitro. Furthermore, azaindole-1 chronic treatment improved hemodynamics and right ventricular hypertrophy in both experimental models of PH. Moreover, the medial wall thickness and muscularization of peripheral pulmonary arteries, as measures of pulmonary vascular remodelling, were significantly ameliorated. Finally, azaindole-1 treatment resulted in a decreased immunoreactivity for phospho-myosin phosphatase target subunit-1 (p-MYPT-1) and proliferating cell nuclear antigen (PCNA) in pulmonary vessels of monocrotaline-injected rats, suggesting an impaired ROCK activity and reduced proliferating vascular cells.In conclusion, azaindole-1 provided therapeutic benefit in experimental PH and this may be attributable to its potent vasorelaxant and antiproliferative effects. Thus, azaindole-1 may offer a useful approach for the treatment of pulmonary hypertension and may have a potential clinical application.

Pulmonaler Hochdruck (PH) ist eine schwere chronische und lebensbedrohliche Erkrankung, charakterisiert duch progressive Zunahme des pulmonal arteriellen Drucks, welche letztlich in Rechtsherzversagen und Tod endet. PH hat besitzt eine komplexe Pathologie mit der Kombination eines Remodelling der Pulmonalgefäße, Vasokonstriktion und in situ Thrombose. Der Schlüssel zu der Schwere dieser Erkrankung ist das progressiv verlaufende Gefäßremodelling. Dieses progressive pulmonale Gefässremodelling ist das Attribut der PH Pathologie und wird charakterisiert durch Abnormalitäten der Gefäßzellen, wie zB. Verstärkte Proliferation, Migration, und Unempfindlichkeit gegenüber Apoptose. Obwohl die PH Pathologie Gegenstand intensiver Forschung ist, sind die genauen molekularen Mechanismen noch nicht vollständig verstanden. Eine erfolgreiche Therapie zur Heilung dieser schweren Krankheit ist noch nicht verfügbar. Rho-kinasen (ROCK) scheinen in der Pathologie der PH eine wichtige Rolle zu spielen und lassen vermuten, hier einen erfolgsversprechenden Angriffspunkt für eine mögliche Therapie darzustellen.Im Einklang mit dementsprechender Literatur, erforschen unsere Studien im Tiermodell den therapeutischen Effekt des hochselektiven, oral verfügbaren ROCK Inhibitors, Azaindole-1. Wir konnten erfolgreich zeigen, dass Azaindole-1 die Vasokonstriktion in isolierter, ventilierter und Puffer-perfundierter Mauslunge sowie die Proliferation von arteriellen glatten Muskelzellen der Ratte in vitro verminderte. Weiterhin verbesserte eine Behandlung mit Azaindole-1 die Hämodynamik und Rechtsherzhypertrophie in zwei Tiermodellen der PH. Ebenfalls kam es zu einer signifikanten Verbesserung der medialen Wandstärke sowie dem Muskularisierungsgrad der Pulmonalgefäße, welche als Paramater für das vaskuläre Remodelling gelten. Letztlich führte eine Behandlung mit Azaindole-1 zu einer Abnahme der Immunreaktivität der Phospho-Myosin Phosphatase Target Subunit-1 (p-MYPT-1) und PCNA (prolferating cell nuklear antigen) in Pulmonalgefäßen der mit Monocrotalin injizierten Ratten, was auf eine geminderte ROCK Aktivität und reduzierte Anzahl proliferierender Gefäßzellen schließen lässt.Zusammenfassend lässt sich sagen, dass Azaindole-1 ein vielversprechender Ansatz für die Behandlung experimenteller PH darstellt, was sich wahrscheinlich auf seine potenten vasorelaxierenden und antiproliferierenden Effekte zurückführen lässt. Dadurch könnte Azaindole-1 einen guten Therapieansatz für die Behandlung des pulmonalen Hochdrucks darstellen und das Potential für eine klinische Anwendung besitzen.
Effekt von Rho-kinase Inhibition in chronisch experimenteller pulmonaler Hypertonie
Keywords: ddc:610